Dye pH variation on blueberry anthocyanin based dye sensitized solar cell - Zainul Abidin; Eka Maulana; Panca Mudjirahardjo; M. Ivan Fadillah (Institute of Advanced Engineering and Science, 2020)
Anthocyanin is a type of natural pigment that gives color to plants and can be used to absorb visible light with wavelength of 400-600 nm. The absorption ability is very useful for dye in designing dye sensitized solar cell (DSSC). The anthocyanin can be extracted from blueberry and has unique characteristic of high stability when it reaches low pH. In this paper, design of DSSC with dye made of blueberry anthocyanin and its performance related to pH variation is presented. The performance was evaluated experimentally according to output voltage and current generated by 4 fabricated samples (pH of 1.5, 2, 2.6, 4.4) from A.M 1.5 sunlight and 10-watt LED. Experiment results show that for both light sources, dye with pH of 1.5 has the highest output voltage and current among the others. Since the output voltage and current are very small, the exsisting design of DSSC is suitable to be developed for optical sensor.